Comprehensive analysis of on-sun catalytic reforming of methane with a hydroxyapatite-supported nickel catalyst in a tubular solar reactor - Chuayboon, Srirat; Kulporm, Ratikorn; O-Thong, Sompong; Pham Minh, Doan; Abanades, Stéphane (My University, 2026)
Methane reforming offers a suitable pathway for greenhouse gas utilization, but its implementation is hindered by catalyst deactivation due to carbon deposition and thermal sintering. This study shows that hydroxyapatite serves as a stable catalytic support for solar-driven dry, steam, and dual reforming. The influence of oxidizer type and concentration (H2O, CO2, H2O/CO2 mixture) is experimentally investigated at 800 °C in a tubular solar reactor. A hydroxyapatite-supported nickel catalyst (Ni/HA) achieves methane conversion exceeding 95% with 95% H2 and 96% CO selectivity. An excess of oxidant (oxidant/CH4 mole ratio of 1.2-1.5) is recommended to promote CH4 conversion, improve solar reactor performance, and prevent carbon formation and catalyst deactivation. Through sequential on-sun experimental runs, energy upgrade factor above 1.5 and solar-to-fuel efficiency over 20% are attained, demonstrating high catalytic performance stabilized by the metal dispersion on the support. Dual reforming exhibits the highest syngas yield and performance, with minimized carbon formation and H2/CO ratio approaching 2.0. Catalyst characterization (XRD, FTIR, SEM, TEM/EDX) confirms high thermal/chemical stability of Ni/HA under solar heating conditions. These results demonstrate compatibility of Ni/HA catalyst with solar methane reforming, providing a high-efficiency sustainable system for converting greenhouse gases into syngas.
Keywords: Catalytic reforming; CO2removal; Greenhouse gas utilization; Solar fuel; Solar reactor; Thermochemical conversion